Terpenes as bacterial efflux pump inhibitors: A systematic review - Dias, Kaio Jefté Santos De Oliveira; Miranda, Gustavo Marinho; Bessa, Jonatas Reis; Araújo, Ana Carolina Justino De; Freitas, Priscilla Ramos; Almeida, Ray Silva De; Paulo, Cícera Laura Roque; Neto, José Bezerra De Araújo; Coutinho, Henrique D. M.; Ribeiro-Filho, Jaime (Frontiers in Pharmacology, 2022)
Managing antibiotic resistance is a major challenge in modern pharmacotherapy. While molecular analyses have identified efflux pump expression as a significant mechanism underlying multidrug resistance, the targeted drug development has occurred at a slower speed. Thus, considering the verification that terpenes have the ability to enhance the activity of antibiotics against resistant bacteria, the present study gathered evidence pointing to these natural compounds as bacterial efflux pump inhibitors. A systematic search for manuscripts published between January 2007 and January 2022 was carried out using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocol and the following search terms: "Terpene"; AND "Efflux pump"; AND "Bacteria". From a total of 101 articles found in the initial search, 41 were included in this review. A total of 75 different terpenes, 63 bacterial strains, and 22 distinct efflux pumps were reported, with carvacrol, Staphylococcus aureus SA-1199B, and NorA appearing as the most frequently mentioned terpene, bacterial strain, and efflux pump (EP), respectively. The Chi-Squared analysis indicated that terpenes are significantly effective EP inhibitors in both Gram-positive and Gram-negative strains, with the inhibitory frequency being significantly higher in the Gram-positive strains. The results of the present review suggest that terpenes are significant efflux pump inhibitors and as such can be used in drug development targeting the combat of antibacterial resistance.